Gender differences in the typographical features used in the text messaging of young Jordanian undergraduates - Al Rousan, Rafat M.; Abd Aziz, Noor Hashima; Christopher, Anne Althea (2011)
This paper explores gender differences in the typographical features used in the text messaging of young Jordanian undergraduates.Lakoff’s (1975) and Tannen’s (1990) ideas in face-to-face communication, and Herring’s (1994) ideas in computer-mediated communication were taken into consideration.The data were collected from 160 first-year Jordanian undergraduates.Open-ended questionnaires, user diaries, and semi-structured face-to-face interviews were used to collect data.A total of 2,054 text messages were analyzed qualitatively.The data were classified under four typographical features : punctuation, letter and number homophones, phonetic spelling, and emoticons.The analysis reveals that there are gender differences in the text messaging of young Jordanian undergraduates with respect to the use of typographical features.The findings from this study support previous findings about gender differences in the use of language in face-to-face communication and in computer-mediated communication.